Characterisation of spatial variability in water quality in the Great Barrier Reef catchments using multivariate statistical analysis. (December 2018) - Liu, S.; Ryu, D.; Webb, J.A.; Lintern, A.; Waters, D.; Guo, D.; Western, A.W.
Abstract: Water quality monitoring is important to assess changes in inland and coastal water quality. The focus of this study was to improve understanding of the spatial component of spatial-temporal water quality dynamics, particularly the spatial variability in water quality and the association between this spatial variability and catchment characteristics. A dataset of nine water quality constituents collected from 32 monitoring sites over a 11-year period (2006–2016), across the Great Barrier Reef catchments (Queensland, Australia), were evaluated by multivariate techniques. Two clusters were identified, which were strongly associated with catchment characteristics. A two-step Principal Component Analysis/Factor Analysis revealed four groupings of constituents with similar spatial pattern and allowed the key catchment characteristics affecting water quality to be determined. These findings provide a more nuanced view of spatial variations in water quality compared with previous understanding and an improved basis for water quality management to protect nearshore marine ecosystem. Highlights: There is a strong association between spatial pattern in time-averaged water quality and catchment characteristics in the Great Barrier Reef catchments Two clusters of sites are identified based on spatial variability in time-averaged water quality. Particulate constituents show a strong correlation with grazing land use. Oxidised nitrogen shows distinct behaviour in the catchments that might be linked with sugar cane land uses. The results add further evidence to support the current overall direction of water quality management in the Great Barrier Reef catchments.